Ferulago akpulatii (Apiaceae): A new species from Central Anatolia, Turkey - Gürdal, Bahar; Olcay, Bülent; Tuncay, Hüseyi̇n Onur; Akalin, Emi̇ne (Phytotaxa, 2021)
Ferulago akpulatii (Apiaceae) is described as a new species endemic to Central Anatolia, Turkey. It is closely related to Ferulago platycarpa and F. pauciradiata, and is easily distinguished by its cauline leaf shape, inflorescence type, and fruit features. The main morphological differences between Ferulago akpulatii and related taxa are discussed, and the diagnostic characteristics, including the anatomical features of fruits, are given in detail. An identification key of Ferulago akpulatii and the morphologically closer species is also provided.